Plantering av gran (Picea abies) på kalhyggen och självföryngring under högskärmar av björk (Betula pendula och Betula pubescens) : föryngringsresultat 7-10 år efter avverkning - Johansson, Lars (SLU/Dept. of Forest Ecology and Management, 2008)
The aims of the silvicultural method natural regeneration of spruce (Picea abies L. Karst) in birch (Betula pendula and pubescens) shelterwoods are to establish a new stand of tree seedl-ings and to protect those from high groundwater levels, frost damages and grass competition during its first life years. The aim of this work has been to (i) describe how shelterwood and stand characteristics influ-ence the results from using natural regeneration of spruce protected by a shelterwood of birch, and to (ii) compare those regeneration results with planting of spruce after soil scarification in clear-cut areas. Totally 17 harvesting sites have been inventoried and 15 of those included natural regenera-tion in birch shelterwoods, and two were subjects to soil scarification and planting of spruce. The sites represented 7-10 year old final cuts and are located in the coastal (eastern) region of the province of Norrbotten in Sweden. In all areas shelterwood and stand characteristics, as well as the number of main crop seedlings and the height of the highest main crop spruce seedling, were estimated and registered in all areas. Furthermore, each site was divided into vegetation and soil humidity classes. The average number of shelter trees and main crop seedlings were 188 and 1587 per hectare, respectively, but the variation was large. About half (53 %) of the main crop spruce seedlings had been regenerated before the shelterwood cut, and half (47 %) after cut. In parts of the stands that were dominated by Vaccinium-dwarf-shrub vegetation and broadleaved and nar-row-leaved grasses on mesic ground, the numbers of main crop seedlings were lower and the proportion of surfaces empty from seedlings was larger than in those parts of the stands where the vegetation was characterized by Carex and Equisetum species (Sedge/Horsetail-types) and by grass species on moist soils. The regeneration result was not as good in stands on coarse grained soils as in stands on fine grained soils, but this difference was not statistically signifi-cant. The numbers of main crop seedlings were lower in denser shelterwoods but the correla-tion between the number of main crop seedlings and number of shelter trees was very weak and had not significance. Also shelter tree height and basal area had little effect on the regene-ration results. The height of the highest main crop spruce seedling was consistently greater on clear-cuts where soil scarification and planting had been done, than among natural regenerated seedlings in birch shelterwoods, but the difference was not significant. The numbers of main crop seedlings were considerably higher in stands that had mesic soil, were dominated by dwarf-shrub vegetation or grasses and were scarificted and planted than in stands with birch shelterwoods with the same stand characteristics, but this state could not be statistically secured. The large proportion advance growth spruce seedlings indicate that an inventory of these seedlings should be done before shelterwood cutting. A low number of advanced growth seedlings in such an inventory indicate that it is a large risk for unsatisfactory regeneration. The clearly better regeneration results on moist soils, compared to mesic soils, indicate that the later are unsuitable for using natural regeneration with birch shelter trees. The regeneration results in stands that was dominated by dwarf-shrub vegetation and had mesic soils, and were scarificated and planted was better than in stands with birch shelterwood with the same stand characteristics, this result suggests that scarification and planting is a better method to use in sites with these stand characteristics.